Closeness-at-a-distance: Reaching out through pedagogies of making - Jonker, Francois; Newfield, Denise (Critical Studies in Teaching and Learning, 2025)
Elmarie Costandius’s experimental pedagogies challenged the stasis and restriction of top-down, monomodal, cerebral notions of learning, and of knowledge as handed down by experts. The shock delivered by her arts-based approaches was not explosive, but rather a set of vibrations that reconfigured what it means to experiment, traverse, reconfigure, and communicate in classroom events. Her pedagogies fostered encounters with doing, making, and intra-acting as embodied modalities of exploration—approaching new forms of knowing. This article unfolds from our attunement to this gesture of reaching outward. The closeness we seek to approximate emerges from our reaching out towards meaning, memory, and our sense of resonance with Elmarie and each other as kindred companions in thinkingdoingbecoming. We compose this article as a “processual monument” that pays homage to Elmarie’s legacy by advocating for art-based and transmodal practices in higher education pedagogy and inquiry.